Females Are More Resistant to Ischemia-Reperfusion-induced Intestinal Injury Than Males: A Human Study. Issue 6 (December 2020) - Hundscheid, Inca H. R.; Schellekens, Dirk H. S. M.; Grootjans, Joep; Derikx, Joep P. M.; Buurman, Wim A.; Dejong, Cornelis H. C.; Lenaerts, Kaatje
Abstract : Background and Objective: Sex differences in responses to intestinal ischemia-reperfusion (IR) have been recognized in animal studies. We aimed to investigate sexual dimorphism in human small intestinal mucosal responses to IR. Methods: In 16 patients (8 men and 8 women) undergoing pancreaticoduodenectomy, an isolated part of jejunum was subjected to IR. In each patient, intestinal tissue and blood was collected directly after 45 minutes of ischemia without reperfusion (45I-0R), after 30 minutes of reperfusion (45I-30R), and after 120 minutes of reperfusion (45I-120R), as well as a control sample not exposed to IR, to assess epithelial damage, unfolded protein response (UPR) activation, and inflammation. Results: More extensive intestinal epithelial damage was observed in males compared to females. Intestinal fatty acid binding protein (I-FABP) arteriovenous (V-A) concentrations differences were significantly higher in males compared to females at 45I-0R (159.0 [41.0–570.5] ng/mL vs 46.9 [0.3–149.9] ng/mL). Male intestine showed significantly higher levels of UPR activation than female intestine, as well as higher number of apoptotic Paneth cells per crypt at 45I-30R (16.4% [7.1–32.1] vs 10.6% [0.0–25.4]). The inflammatory response in male intestine was significantly higher compared to females, with a higher influx of neutrophils per villus at 45I-30R (4.9 [3.1–12.0] vs 3.3 [0.2–4.5]) and a higher gene expression of TNF-α and IL-10 at 45I-120R. Conclusion: The human female small intestine seems less susceptible to IR-induced tissue injury than the male small intestine. Recognition of such differences could lead to the development of novel therapeutic strategies to reduce IR-associated morbidity and mortality.